Make your own free website on Tripod.com

෤Ԥ͹ؾѹ

1. c 繤Ҥ f 繿ѧѹ f(x) = c f '(x) = 0

٨                         ҡ                     f(x) = C

                                          f(x+h) = c

                          ѧ            f(x+h) - f(x) = c-c = 0

 

      Щ lim           f(x+h) - f(x) = lim          0

                  h-->0                h            h-->0    h

 

                                                    = lim 0 = 0

                                                      h-->0

          蹤                  f '(x) = 0

 

6.gif (472 bytes)

 

2. f 繿ѧ  f(x) = x f ' (x) = 1

٨                     ҡ                        f(x)     =  x

                                      f(x + h)  =  x + h

                              駹       f(x + h) - f(x) = (x+h) - x

                                                        = h

 

Щ      lim           f(x+h) - f(x) = lim           h

                   h-->0                h             h-->0    h

 

                                                     = lim   1

                                                         h-->0

 

                                                     = 1

鹤          f ' (x) = 1

 

6.gif (472 bytes)